Obesity, diabetes, and length of time in the United States: Analysis of National Health and Nutrition Examination Survey 1999 to 2012. Issue 35 (August 2016) - Tsujimoto, Tetsuro; Kajio, Hiroshi; Sugiyama, Takehiro
Abstract : Abstract: Obesity prevalence remains high in the United States (US), and is rising in most other countries. This is a repeated cross-sectional study using a nationally representative sample of the National Health and Nutrition Examination Survey 1999 to 2012. Multivariate logistic regression analyses were separately performed for adults (n = 37, 639) and children/adolescents (n = 28, 282) to assess the associations between the length of time in the US, and the prevalences of obesity and diabetes. In foreign-born adults, the prevalences of both obesity and diabetes increased with the length of time in the US, and ≥20 years in the US was associated with significantly higher rates of obesity (adjusted odds ratio [aOR] 2.32, 95% confidence interval [CI] 1.22–4.40, P = 0.01) and diabetes (aOR 4.22, 95% CI 1.04–17.08, P = 0.04) compared with <1 year in the US. In children/adolescents, obesity prevalence was significantly higher in those born in the US than those who had been in the US for <1 year (aOR 3.15, 95% CI 1.51–6.56, P = 0.002). When analyzed by year, obesity prevalence was significantly higher in US-born than in foreign-born adults from 1999 to 2012. On the other hand, the gap in obesity prevalence between US-born and foreign-born children/adolescents decreased from 1999 to 2011 due to a rapid increase in obesity prevalence among the foreign-born population, until there was no significant difference in 2011 to 2012. This study revealed that the risks of obesity and diabetes have increased in foreign-born US residents with time living in the US. However, the obesity gap between US-born and foreign-born populations is closing. Abstract : Supplemental Digital Content is available in the text